CORPORATE OR SELLER ACCOUNTABILITY IN BLOCKCHAIN AND CRYPTOCURRENCY CORPORATE INVESTMENTS - Evrita, Ella; Maryana, Eny; Lubis, Efridani (jfpublisher, 2022)
The utilization of Information Technology, media, and communication has changed both the behaviour of society and human civilization globally, and the role of law is to regulate social life. At the same time, the digital world provides unlimited space and time for its users; one of the digital developments is related to cryptocurrencies. Cryptocurrency is a digital currency that secured by cryptographic security system. Crypto money can generally used to buy various kinds of digital goods. One of the uses of owning a cryptocurrency is for investment. Currently, the development of cryptocurrencies in Indonesia is swift. Generally, people from upper-middle class already know about the term. The same thing happened in international market. With the background of the rapid development of this cryptocurrency in community, in terms of growth, the obstacles and constraints found, the authors conducted this research, and it is technically challenging to identify the role of each party in current digital business in Indonesia and the existence of a knowledge gap between consumers and producers. This research is descriptive research with normative juridical method, meaning that in discussing existing problems, researchers will look at legislation’s provisions.